Pengaruh FOMO (Fear of Missing Out), Shopping Lifestyle, dan Positive Emotion Terhadap Impulse Buying (Survey pada Mahasiswa Konsumen E-commerce Shopee di Universitas Slamet Riyadi Surakarta) - Ayu Astuti, Nindita; Pratiwi, Adcharina (Teewan Journal Solutions, 2025)
This research aims to analyze the significance of the influence of FoMO (Fear of Missing Out), Shopping Lifestyle, and Positive Emotion on Impulse buying at Shopee. The types of data used in this research are quantitative data. The data sources used are primary and secondary data. The sample in this study was 100 students of Slamet Riyadi University Surakarta. The method used in sampling was purposive sampling or sampling with certain characteristics with a total of 100 samples. Data collection techniques in this research using questionnaires, observations, and literature studies. Test the research instrument using validity test and reliability test. The classic assumption test uses tests: multicollinearity, autocorrelation, heteroscedasticity, and normality. Data analysis techniques using multiple linear regression tests, t tests, F tests, and R2 . The validity and reliability test results show that all statements regarding FoMO (Fear of Missing Out), Shopping Lifestyle, Positive Emotion and Impulse buying are valid because the p-value <0.05 and reliable because Cronbach's alpha> 0.60. The classic assumption test results show that all variables have passed the multicollinearity, heteroscedasticity, autocorrelation and normality tests with normal distribution. The regression analysis results obtained the equation Y = 0.462 + 0.051 X1 + 0.395 X2 + 0.305 X3. The t test results show that fear of missing out (FoMO) (X1) has an insignificant effect on impulse buying at Shopee, shopping lifestyle (X2) and positive emotion (X3) have a significant effect on impulse buying at Shopee. The F test results showed that the regression model used in this study was correct. The R2 test results show that the contribution of the influence of the independent variables X1 (fear of missing out (FoMO)), X2 (shopping lifestyle) and X3 (positive emotion) on Y (impulse buying) is 61.8%. The rest (100% - 61.8%) = 38.2% is explained by other variables outside the model.